Green Economy and Job Commitment of Managers and Accountants in Small Scale Enterprises in Owerri (West African Journal on Sustainable Development, 2024)
Sustainable economy has always taken its position as the hinge on which national and organizational outcomes rotate. However, many research gaps have been observed in the area of green economy in Nigeria. The objectives of the study therefore, are to examine the relationship between effective waste management and job commitment of Managers and Accountants in small scale enterprises in Owerri; and evaluate the level of correlation between renewable energy and job commitment of Managers and Accountants in small scale enterprises in Owerri. The study is guided by two research questions and two hypotheses. The research employs the survey research design. A structured questionnaire is the major instrument for data collection. The study uses Cronbach Alpha statistic for obtaining 0.79 as the reliability ratio of the survey instrument. The researcher commits data analysis to descriptive statistics of mean and standard deviation and employs correlation analysis for testing hypotheses. The findings show that there is a significant relationship between effective waste management and job commitment of Managers and Accountants; and there is significant level of correlation between renewable energy and job commitment of Managers and Accountants in small scale enterprises in Owerri. The study concludes that green economy positively and significantly correlates with job commitment of Managers and Accountants in small scale enterprises in Owerri. The study recommends that management of small scale enterprises should always adopt sustainable, healthy and environmentally friendly approaches for waste management so as to enhance the job commitment of their workforce especially the Managers and Accountants. Enterprises should invest heavily on renewable energy as it guarantees uninterrupted power supply thereby enhancing the job outcomes of Managers and Accountants especially their commitment to their jobs.
Keywords: Green economy; Job commitment; Waste management; Renewable energy